Flexibility of the Superficial Circumflex Iliac Artery Perforator Free Flap for Hand Reconstruction - Linh Tuan To, MD, MSc; Tuan-Anh Hoang, MD, DDS, PhD; Ha Hong Nguyen, MD, PhD; Son Thiet Tran, MD, PhD; Sung-Kiang Chuang, DMD, MD, DMSc; Kevin C. Lee, MD, DDS (Plastic and Reconstructive Surgery, Global Open)
Background:. The superficial circumflex iliac artery perforator (SCIP) flap has several advantages in hand reconstruction. It is thin and pliable, the extensive branching of the arterial system allows for multiple components, and the donor site can be closed inconspicuously. This article reports our experience using the SCIP flap for hand reconstruction, and we highlight the flexibility of the SCIP for extended and chimeric flaps. Methods:. We conducted a retrospective cohort study from November 2022 to January 2024 of patients with complex hand defects (exposure and/or defect of the bone or tendon) who underwent reconstruction with an SCIP flap. The plane of dissection was above the layer of superficial fascia. In overweight patients, the superficial fat lobules were removed under the microscope to thin the flap. Tailoring, chimeric, and supercharged flaps were constructed as needed for complicated hand defects. Data collected included defect characteristics, flap design, and outcomes. Results:. A total of 44 flaps were performed on 43 patients. The average flap length was 17.8 cm (range 10–42 cm), the average flap width was 7.6 cm (range 2–11 cm), and the average flap thickness was 2.5 mm (range 2–4 mm). Hand defects were reconstructed with 9 chimeric flaps, 8 tailored flaps, 3 chimeric and tailored flaps, and 2 supercharged flaps. Overall, 42 flaps (95.5%) survived and 2 flaps (4.5%) experienced necrosis. Conclusions:. The SCIP flap is a reliable option for complex hand defect reconstruction. This technique can provide a large, thin, pliable skin paddle incorporating components from the external oblique fascia and iliac bone. We did not encounter any recurrent issues when using it as a supercharged flap, tailored flap, or chimeric flap. Reconstructive surgeons should develop comfort with the SCIP flap in hand reconstruction given its versatility.